The Mpowerment Of Cadres Influence On Knowledge And Attitude Of Mothers In Breasting In Bengkulu City - wisuda andeka marleni; Linda (Avicenna: Jurnal Ilmiah, 2022)
WHO has established 7 contacts with lactation counselors or lactation clinics from pregnant women to babies born and breastfeeding. With enough information about breastfeeding and breastfeeding, mothers and families are expected to be ready to undergo the process of breastfeeding later. The Cadre Empowerment Program is a community empowerment program by conducting mentoring activities to increase knowledge and understanding of family planning through counseling, guidance and counseling so that postpartum mothers can carry out her nature in providing nutrition to their children. This research is a quantitative study, using quasi-experimental research designs with a pre-post control group. The sample of this study was 36 respondents, namely 18 people in the cadre empowerment group (intervention) and 18 people without cadre empowerment (control). The research instrument used a questionnaire of knowledge and attitudes about breastfeeding. Bivariate statistical tests use the Wilcoxon Test. The results showed that in the intervention group it was known that the majority (83.3%) were aged 20-35 years, the majority (66.7%) with secondary education (high school) and the majority (72.2%) were multiparous. There is a significant influence between the Empowerment of Cadres to the Knowledge and Attitudes of Mothers in Giving ASI in the City of Bengkulu with p = 0.002 Collaboration of MCH health personnel and Health Cadres in improving the attainment of knowledge and attitudes of mothers in breastfeeding in Bengkulu City can be through empowering health cadres. Keywords: Empowerment of Cadres, Knowledge and Attitudes, ASI